The Extension of Philosophical-Anthropological Foundations in the Transformation of Human Sciences Based on Imam Khomeini’s Intellectual System - Amin Dehghani; Abdolhossein Khosropanah (آموزه‌‌های فلسفه اسلامي)
Human anthropology forms the core of the human sciences. Research in this area is a prerequisite for any theory-building and transformation within the human sciences. Imam Khomeini, as a prominent and influential social thinker, possesses a coherent thought system. One of the key aspects of his philosophy is his philosophical and rational foundations. In the philosophical foundations, human anthropology is one of the most important elements that has a direct and fundamental impact on all human sciences. The research question is: What are Imam Khomeini’s foundations in the field of human anthropology, and how have they extended into the transformation of the human sciences? This article aims to delineate these foundational aspects in two areas: "The Philosophical Foundations of Imam Khomeini’s Human Anthropology" and "The Extension of These Foundations in the Transformation of Human Sciences." Within the article, the details of these two areas are addressed. These philosophical foundations have implications that must be established and extended for the transformation, elevation, and formation of the ideal human sciences. Therefore, this article can serve as an original introduction to the extension of Imam Khomeini’s thought in the transformation and elevation of human sciences, providing a broad application in human sciences and issues related to society, national systems, and civilization.